Luminescence and radiation-induced defects in Li₂B₄O₇:Eu single crystals - Dubovik, M.F.; Tolmachev, A.V.; Grinyov, B.V.; Grin, L.A.; Dolzhenkova, E.F.; Dobrotvorskaya, M.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Thermostimulated luminescence (TSL) of Li₂B₄O₇ and Li₂B₄O₇:Eu single crystals in the temperature range 290-650K has been studied. Lithium tetraborate (LTB) doped with europium has been found to favour a further increase of the light sum storage of electron-captured centres. Radiation-induced defects and their participation in recombination process in LTB:Eu are considered. Suggestions about character of Eu site in the host lattice based on the photoluminescence spectral data are discussed. The electron structure of LTB crystals measured by XPS method is presented.